2020
DOI: 10.1111/andr.12814
|View full text |Cite
|
Sign up to set email alerts
|

p53 and MDM2 expression in primary and metastatic testicular germ cell tumors: Association with clinical outcome

Abstract: Background Testicular germ cell tumors (TGCTs) are highly sensitive to platinum‐based chemotherapy, and wild‐type p53 seems to play a pivotal role in this susceptibility. On the other hand, overexpression of MDM2 seems to entail treatment resistance and unfavorable prognosis. Objectives We aimed to describe p53 and MDM2 immunoexpression in a well‐characterized cohort of primary and metastatic TGCTs and evaluate associations with clinicopathological and prognostic variables, including survival. Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In addition, despite the curative success of GCTs due to their sensitivity to chemotherapeutics such as cisplatin, GCTs may acquire resistance which, with the lack of targeted treatment, is inherently difficult to treat and exemplifies a significant shortcoming in current GCT treatment [383]. Thus, a significant proportion of GCT research aims to identify the underlying cause of GCT resistance, and it has been suggested that the deregulation of the P53 pathway may be a contributing factor [15,18,39,40,42]. Correspondingly, multiple mechanisms of P53 pathway deregulation have been observed in GCTs including rare TP53 mutations and elevated P21, MDM2, and/or MDM4 levels, which have also been associated with resistance to cisplatin [22,27,34,37,39,384].…”
Section: Summarizing Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, despite the curative success of GCTs due to their sensitivity to chemotherapeutics such as cisplatin, GCTs may acquire resistance which, with the lack of targeted treatment, is inherently difficult to treat and exemplifies a significant shortcoming in current GCT treatment [383]. Thus, a significant proportion of GCT research aims to identify the underlying cause of GCT resistance, and it has been suggested that the deregulation of the P53 pathway may be a contributing factor [15,18,39,40,42]. Correspondingly, multiple mechanisms of P53 pathway deregulation have been observed in GCTs including rare TP53 mutations and elevated P21, MDM2, and/or MDM4 levels, which have also been associated with resistance to cisplatin [22,27,34,37,39,384].…”
Section: Summarizing Discussionmentioning
confidence: 99%
“…For instance, GCTs most often express high levels of wild-type (WT) TP53, and it has been suggested that the P53 pathway is (partially) responsible for their characteristic to enter apoptosis in response to platinum-based chemotherapeutics (e.g., cisplatin) which is reminiscent of ES cells in response to DNA damage [10,18,21,23,[25][26][27][28][29][33][34][35][36][37]. In addition, it has been suggested that the P53 pathway is deregulated through multiple mechanisms in GCTs that have acquired resistance to chemotherapy, including cisplatin [15,18,[38][39][40][41][42].…”
Section: Introduction 1embryonic Stem Cells and Germ Cell Tumors Versus Somatic Cellsmentioning
confidence: 99%
“…Moreover, there have been several reports that MDM2 amplifications are enriched in cisplatin-resistant tumors by inactivating p53 and its proapoptotic program, which is supported by the efficacy of MDM2 inhibitor Nutlin-3 in cisplatin-resistant cases, promoting sensitivity to cisplatin [ 108 , 109 , 110 ]. Studies focusing solely on immunohistochemistry for p53 and MDM2 in primary tumors have been conflicting, some failing to show ability to predict disease recurrence after cisplatin treatment and others showing up- and downregulations of MDM2/p53, respectively [ 70 , 111 , 112 , 113 ]. Current knowledge indicates the p53 pathway as a contributor to the cisplatin resistance phenotype but not solely responsible for cisplatin resistance.…”
Section: Dissecting Cisplatin Resistance Mechanismsmentioning
confidence: 99%
“…Their common precursor is germ cell neoplasia in situ (GCNIS), and they are divided into seminomas (SE) and non-seminomas (NS). The latter comprise a complex array of subtypes that include embryonal carcinoma (EC), choriocarcinoma (CH), yolk sac tumor (YST), and teratoma (TE) [1][2][3][4][5][6][7]. Overall, TGCTs represent a model of curable disease, with most patients presenting with stage I disease (around 70%), but approximately 75% of these are cured with orchiectomy alone, without the need for subsequent adjuvant treatments [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, TGCTs represent a model of curable disease, with most patients presenting with stage I disease (around 70%), but approximately 75% of these are cured with orchiectomy alone, without the need for subsequent adjuvant treatments [4,8,9]. For those who require systemic therapy, TGCTs present extreme sensitivity to cisplatin-based chemotherapy, due to their unique molecular background [3,10]. However, a significant group of patients relapse, most frequently within the first two years after initial diagnosis [9,11].…”
Section: Introductionmentioning
confidence: 99%